2011
DOI: 10.1002/hrdq.20062
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of human resource development research across disciplines: A citation and content analysis

Abstract: The primary purpose of the current study is to identify how human resource development (HRD) research has contributed to the knowledge base across social science disciplines during the past two decades. We identified the top 20 Academy of Human Resource Development (AHRD) journal articles that have been most frequently cited in research articles published in journals other than the four AHRD journals. With the use of content analysis of the most-cited articles, three key research themes were identified: (a) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 74 publications
(84 reference statements)
3
51
0
Order By: Relevance
“…A direct content analysis (Hsieh and Shannon, 2005) was conducted to classify the papers. The reliability of the allocation of articles in each category was addressed following the two-step procedure used in other content analyses such as Furrer, Thomas and Goussevskaia (2008), Jeung et al (2011) and Clark et al (2014). The reliability of the allocation of articles in each category was addressed following the two-step procedure used in other content analyses such as Furrer, Thomas and Goussevskaia (2008), Jeung et al (2011) and Clark et al (2014).…”
Section: An Overview Of Research Approaches In the Hrm−performance LImentioning
confidence: 99%
“…A direct content analysis (Hsieh and Shannon, 2005) was conducted to classify the papers. The reliability of the allocation of articles in each category was addressed following the two-step procedure used in other content analyses such as Furrer, Thomas and Goussevskaia (2008), Jeung et al (2011) and Clark et al (2014). The reliability of the allocation of articles in each category was addressed following the two-step procedure used in other content analyses such as Furrer, Thomas and Goussevskaia (2008), Jeung et al (2011) and Clark et al (2014).…”
Section: An Overview Of Research Approaches In the Hrm−performance LImentioning
confidence: 99%
“…Several scholars in the field of HRD have used citation analysis to examine the impact of research among disciplines (e.g., Azevedo & Hedayati, 2013; Ghosh et al, ; Jeung et al, ; Jo et al, ; Sleezer & Sleezer, ; Sun & Wang, ). Using citation analysis, Sleezer and Sleezer () investigated the status of research in HRD in the United States through the years 1980–1994 and reported a list of 17 journals that published more than 15 HRD related articles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using citation analysis, Jeung et al () examined key research areas that HRD has contributed to for 20 years, and identified the top 20 most frequently cited HRD articles by other journals. The three key research areas were training transfer and evaluation, learning in organizations, and knowledge sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the introduction to this article, a number of important developments in HR research and practice are highlighted, such as a greater interest in strategic HRM and HRD (Boxall and Purcell, 2011;Garavan, 2007), demands for a tighter fit between HR and organisations' strategies and goals (Ulrich et al, 2009), and a growing focus on change and development activities in organisations Jeung et al, 2011) -particularly with respect to HR activities that may foster different types of innovation (Beugelsdijk, 2008;Jiang et al, 2012;Shipton et al, 2005). Furthermore, it has been argued that research should assume a more holistic and integrative approach to both HRM and HRD concepts-and to specific HR activities -instead of considering them isolated practices (Laursen, 2002;Laursen and Foss, 2003;Ruona and Gibson, 2004).…”
Section: The Hr Supply Chainmentioning
confidence: 99%